Experiências, mediações e posições políticas: a luta por moradia no Campo Belo-Campinas/SP - Formagio, Cessimar de Campos (2012)
The relationship between State and popular movements is drawn on the political and economical conjuncture of a historical moment and also by the political position that a movement assumes in front of the state projects, in which the interests of hegemonic corporate groups are represented. Considering the observation of Sader (1995:41) on the "wide range of possible answers facing the same given request", this research seeks to understand how the movement of struggle for housing of residents from Campo Belo Jardim on the outskirts of Campinas organizes and positions itself, and how the State deals with such specific profile of organization, in the attempt to create among residents some degree of consensus on the expansion project at the airport of Viracopos and mitigate the resistance of residents to the expropriation of the place where they live. On a broader plan the research aims to analyze the relationship between the profile of internal organization of a popular movement and the relations it establishes with the State. We seek therefore, to point out the different political positions among residents of Campo Belo and how these positions interact in the formation of one of the major political mediation spaces in the neighborhood residents' associations. To identify the nuances of the relationship between associations and State, we analyze the course of the struggle for the residents permanency in the neighborhood, which is threatened by the expansion of Viracopos airport. The research was built up from three clusters: the bibliographic selection; the fieldwork conducted in thirteen months (November 2009 to December 2010) from living together with the neighborhood s residents and doing a follow up on the neighborhood associations; and the documentary research, which involved organizing documents from associations, consulting the collection/acquis of the city s newspapers and photos produced in the field work, part of this material is in the annexes of this dissertation.